Identification of Saponins from the Active Fraction Sea Cucumbers (Stichopus vastus sluiter) - M Irwan Sapta Purna Bintang; Mery Sukmiwati; Rahman Karnila (Faculty of Fisheries and Marine, Universitas Riau, 2023)
This study aims to determine the secondary metabolic content of saponin contained in the active fraction of sea cucumber (Stichopus vastus) by using metabolic test reagents and thin-layer chromatography (TLC) analysis. The active fraction was given the reagent in the form of HCl 2N and strong acid then continued with analysis to determine the Rf value and lieberman-burchad reaction. The results of the metabolic reaction test showed that the active fraction contained steroidal saponin compounds characterized by the presence of a stable foam and the formation of a greenish-green color. TLC analysis produced a single stain with an Rf value of 0.9 and a bluish color reaction after being given Liberman-burchad which confirmed that the saponins contained in the active fraction of sea cucumbers were steroidal saponin